2018
DOI: 10.1108/mrr-07-2017-0212
|View full text |Cite
|
Sign up to set email alerts
|

Exploring antecedents of social media usage in B2B: a systematic review

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 131 publications
(260 reference statements)
0
33
0
Order By: Relevance
“…For example, Agnihotri et al (2016) investigated how the implementation of social media by B2B salesperson affects consumer satisfaction. Salesperson's social media use is defined as a "salesperson's utilization and integration of social media technology to Agnihotri et al 2016;Ancillai et al 2019;Rossmann and Stei 2015;Agnihotri et al 2012;Agnihotri et al 2017;Itani et al 2017;Salo 2017;Bhattacharjya and Ellison 2015;Gáti et al 2018;Gruner and Power 2018;Hollebeek 2019;Iankova et al 2018;Jussila et al 2011;Kho 2008;Niedermeier et al 2016;Ogilvie et al 2018;Hsiao et al 2020;Mahrous 2013;Kärkkäinen et al 2011;Meire et al 2017;Moncrief et al 2015;Rodriguez et al 2012;Pitt et al 2018;Pitt et al 2017;Sivarajah et al 2019 Adoption of social media Buratti et al 2018;Gáti et al 2018;Gazal et al 2016;Itani et al 2017;Kumar and Möller 2018;Lacka and Chong 2016;Lashgari et al 2018;Michaelidou et al 2011;Müller et al 2018;Nunan et al 2018;Pascucci et al 2018;Rossmann and Stei 2015;Shaltoni 2017;Siamagka et al 2015;…”
Section: Customer Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Agnihotri et al (2016) investigated how the implementation of social media by B2B salesperson affects consumer satisfaction. Salesperson's social media use is defined as a "salesperson's utilization and integration of social media technology to Agnihotri et al 2016;Ancillai et al 2019;Rossmann and Stei 2015;Agnihotri et al 2012;Agnihotri et al 2017;Itani et al 2017;Salo 2017;Bhattacharjya and Ellison 2015;Gáti et al 2018;Gruner and Power 2018;Hollebeek 2019;Iankova et al 2018;Jussila et al 2011;Kho 2008;Niedermeier et al 2016;Ogilvie et al 2018;Hsiao et al 2020;Mahrous 2013;Kärkkäinen et al 2011;Meire et al 2017;Moncrief et al 2015;Rodriguez et al 2012;Pitt et al 2018;Pitt et al 2017;Sivarajah et al 2019 Adoption of social media Buratti et al 2018;Gáti et al 2018;Gazal et al 2016;Itani et al 2017;Kumar and Möller 2018;Lacka and Chong 2016;Lashgari et al 2018;Michaelidou et al 2011;Müller et al 2018;Nunan et al 2018;Pascucci et al 2018;Rossmann and Stei 2015;Shaltoni 2017;Siamagka et al 2015;…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…The study by Pascucci et al (2018) conducted a systematic literature review on antecedents affecting the adoption and use of social media by B2B companies. By reviewing 29 studies published in academic journal and conferences from 2001 to 2017, the study identified external (pressure from customers, competitors, availability of external information about social media) and internal factors (personal characteristicsmanagers age, individual commitment, perceptions of social media-perceived ease of use, perceived usefulness, perceived utility), which can affect adoption of social media.…”
Section: Adoption Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…A wide set of theories (e.g., diffusion of innovation, technology acceptance and value-added models) has been mobilized in the literature to investigate how different B2B market-actors comprehend SMTs, which are developed, codified, and retained to seize socially generated values that enhance knowledge management processes and help organizations compete (Pascucci et al 2018 ; Golden 2011 ). In a professional context, employees’ knowledge sharing via SMT is an investment in social relationships and represents individual market actor’s experiential know-how (work, actions, and sociality-based practices [Marwick and Hargittai 2019 ]) shared during social interactions (Panahi et al 2016 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This is evidenced by the growing number of research output within academic journals and conference proceedings. Some studies provided a comprehensive literature review on social media use by b2b companies [4,7], but focused only on the adoption of social media by b2b or social media influence, without providing the whole picture of the use of social media by b2b companies. Thus, this study aims to close this gap in the literature by conducting a comprehensive analysis of the use of social media by b2b companies.…”
Section: Introductionmentioning
confidence: 99%